Empowering self-concept among felda students: A nominal group technique approach using Rational Emotive Behavior Therapy (REBT) - Mohd Sahell, Akrimi Maswa; Khalid, Nurul Fazzuan; Syed Abdullah, Syed Mohamad; Ahmad, NorShafrin (Journal of Islamic, Social, Economics and Development, 2025)
This study explores expert recommendations for addressing low self-concept among FELDA students using Rational Emotive Behaviour Therapy (REBT). The research aims to identify effective interventions and strategies, grounded in REBT, which can enhance the self-concept of students from marginalised rural communities. A Nominal Group Technique (NGT) was employed to gather expert opinions on potential interventions, involving a diverse group of seven professionals from counselling, education, and psychology. The study found broad consensus among the experts on a set of ten interventions, including cognitive restructuring, self-acceptance promotion, behavioural activation, and mindfulness practices. These interventions were viewed as essential for challenging irrational beliefs, fostering emotional regulation, and providing social support to students. The findings indicate that a holistic approach, combining mental and social support, is crucial for improving FELDA students’ self-concept and overall development. Furthermore, the study recommends future research to evaluate the long-term impact of these strategies, explore other factors influencing self-concept, such as family and cultural backgrounds, develop culturally appropriate psychological assessment tools for FELDA students, and investigate the use of technology, such as online counselling, to better support rural students. In conclusion, this study highlights the potential of the REBT approach in boosting the confidence and potential of FELDA students, helping them overcome social and educational challenges while achieving personal growth and success.